Significantly lower mean serum vitamin B12 and folic acid levels and a significantly higher frequency of serum iron deficiency in younger than in older atrophic glossitis patients - Yu-Hsueh Wu; Yang-Che Wu; Julia Yu-Fong Chang; Yi-Pang Lee; Chun-Pin Chiang; Andy Sun (Elsevier, 2022)
Background/purpose: : Our previous study found that 19.0%, 16.9%, 5.3%, 2.3%, and 11.9% of 1064 atrophic glossitis (AG) patients have anemia, serum iron, vitamin B12, and folic acid deficiencies, and hyperhomocysteinemia, respectively. This study mainly evaluated the anemia, hematinic deficiencies, and hyperhomocysteinemia in 224 younger (≤50 years old) and 840 older (>50 years old) AG patients. Materials and methods: The blood hemoglobin (Hb) and serum iron, vitamin B12, folic acid, and homocysteine levels in 224 younger and 840 older AG patients were measured and compared with the corresponding levels in 112 younger (≤50 years old) and 420 older (>50 years old) healthy control subjects (HCSs), respectively. Results: We found that 224 younger AG patients had significantly lower mean blood Hb and serum iron levels than 112 younger HCSs. Moreover, 840 older AG patients had significantly lower mean blood Hb and serum iron levels and a significantly higher mean serum homocysteine level than 420 older HCSs. In addition, 224 younger AG patients had significantly lower mean serum vitamin B12 and folic acid levels, a lower mean serum homocysteine level (marginal significance, P = 0.056), a significantly higher frequency of serum iron deficiency, and a significantly lower frequency of hyperhomocysteinemia than 840 older AG patients. Conclusion: The younger AG patients do have significantly lower mean serum vitamin B12 and folic acid levels, a significantly higher frequency of serum iron deficiency, and a significantly lower frequency of hyperhomocysteinemia than the older AG patients.